2022
DOI: 10.3390/insects13020174
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Hormone Synthesis Pathway Gene SfIPPI Regulates Sogatella furcifera Reproduction

Abstract: The juvenile hormone (JH) is crucial for insect reproduction, and isopentenyl pyrophosphate isomerase (IPPI) is a key enzyme in the JH synthesis pathway. However, few studies have investigated how IPPI regulates insect reproduction. This study identifies and characterizes the IPPI gene (SfIPPI) from the important agricultural pest Sogatella furcifera. A phylogenetic analysis reveals a high homology of SfIPPI with the IPPI amino acid sequences of Laodelphax striatellus and Nilaparvata lugens (Stål). Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that AaIPPI plays a critical role in the synthesis of JH in A. aegypti , and changing the AaIPPI mRNA levels inhibits JH biosynthesis ( Diaz et al 2012 ). The SfIPPI protein is involved in female reproduction, and silencing SfIPPI had a negative effect on ovarian development and egg production in Sogatella furcifera ( Gong et al 2022a ). The above studies have shown that IPPI plays a certain role in female reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that AaIPPI plays a critical role in the synthesis of JH in A. aegypti , and changing the AaIPPI mRNA levels inhibits JH biosynthesis ( Diaz et al 2012 ). The SfIPPI protein is involved in female reproduction, and silencing SfIPPI had a negative effect on ovarian development and egg production in Sogatella furcifera ( Gong et al 2022a ). The above studies have shown that IPPI plays a certain role in female reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…In Caenorhabditis elegans , IPPI is critical for viability, the mutation of isopentenyl-diphosphate isomerase Idi-1 blocked larval growth and development ( Yochem et al 2005 ). In Sogatella furcifera (Horvath) (Hemiptera, Delphacidae), the IPPI gene is involved in the female reproduction process, and knockdown of the SfIPPI significantly blocks ovarian development and egg production ( Gong et al 2022b ). In addition, IPPI is involved in the JH synthesis process in Aedes aegypti ( Diaz et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…28 Additionally, research has shown that silencing SfVg and SfVgR significantly reduces the number of laid eggs and the hatching rates. 29 Furthermore, knocking down genes related to JH biosynthesis (i.e., SfHMGR, SfJHAMT, SfIPPI and SfFAMeT) and JH signal transduction (SfMet and SfKr-h1) significantly inhibits ovarian development and the number of laid eggs in S. furcifera, [30][31][32][33][34] indicating that genes related to JH signaling pathways are also involved in reproductive regulation. Additionally, it has been found that the TOR signaling pathway also participates in regulating the reproduction of S. furcifera.…”
Section: Introductionmentioning
confidence: 99%